Pemberdayaan UMKM Berbasis Kolaborasi: Strategi Model Bazar untuk Meningkatkan Ekonomi Lokal di Desa Ngenep - Khotimah, Siti Khusnul; Savitri, Intan Dewi; Rusmawati, Roosi; Ilham, Hazel Muhammad; Radhya, Aufa; Ayaza, Melika; Kanistha, Shafwah Allya; Daniella G, Princess Beatrix; Tasyakurina, Maritza Inas (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2025)
The ‘Pamitran’ MSME Bazaar held in Ngenep Village, Karangploso District, Malang Regency, is a strategic initiative for local economic empowerment and MSME development in the village. Through collaboration between various parties—lecturers, students, PKK groups, village officials, professionals, and MSME actors—this activity has successfully created an effective marketing platform for local products. The bazaar activities were not limited to buying and selling transactions but also included various educational and recreational activities, such as French language training for children, coloring competitions, community exercises, dance and music performances, and health services involving the Indonesian Red Cross and doctors. The results of the activity showed that over 85% of SME products were sold, while visitors were also actively engaged in educational and recreational activities. The bazaar successfully raised public awareness about the importance of supporting local products, introduced village-specific products, and strengthened social networks among SME operators and the community. Through the synergy between various elements, this activity demonstrated that cross-sectoral collaboration can be a key factor in the sustainable development of village economies.